Impact of Food Assistance Programs on Obesity in Mothers and Children: A Prospective Cohort Study in Peru. - Carrillo Larco, Rodrigo M (2016)
Objectives. To assess obesity risk among mothers participating in Community Kitchens and children participating in Glass of Milk (Peru food assistance programs). Methods. We analyzed prospective data from the Young Lives study. The exposure consisted in varying degrees of benefit from any of the programs (no participation in any of the programs, program participation for some months, or program participation nearly every month) at baseline (2006–2007). The outcome was overweight and obesity in mothers and children at follow-up (2009–2010). Results. Prevalence of childhood overweight and obesity was 15.5% and 5.1%, respectively; the corresponding figures for mothers were 40.5% and 14.6%. Children exposed nearly every month to the Glass of Milk program had a 65% lower risk of becoming obese compared with children not participating in the program (relative risk [RR] = 0.35; 95% confidence interval [CI] = 0.18, 0.66). Mothers participating frequently in the Community Kitchens program had almost twice the risk of becoming obese compared with those who did not participate (RR = 1.93; 95% CI = 1.18, 3.15). Conclusions. Participating in food assistance programs in Peru was associated with a lower risk of obesity in children and greater risk of obesity in mothers.